2021
DOI: 10.3390/educsci11030094
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Requests for Information by Preschoolers with and without Language-Based Disabilities

Abstract: We report two experiments on the emission of questions to request the names of unfamiliar stimuli by preschoolers. In the first experiment, 19 preschoolers with and without disabilities served as participants. Experiment 1 was a descriptive analysis of whether or not the 19 participants asked questions about unfamiliar pictures and objects in one-to-one and group settings. These were dependent variables in the second experiment as well. Four participants, who did not ask any questions in the first experiment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Speckman et al. (2021) had only one experiment that met our inclusion criteria (Experiment 2); therefore, we only included information about the respective experiment. Three of these articles included two experiments (Carnett et al., 2020; Endicott & Higbee, 2007; Sundberg et al., 2001).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Speckman et al. (2021) had only one experiment that met our inclusion criteria (Experiment 2); therefore, we only included information about the respective experiment. Three of these articles included two experiments (Carnett et al., 2020; Endicott & Higbee, 2007; Sundberg et al., 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The authors of 17 experiments reported assessments (e.g., Vineland Adaptive Behavior Scales, Sparrow et al., 2005; VB‐MAPP, Sundberg, 2008; Preschool Language Scale, Zimmerman et al., 2002) to evaluate the participants' verbal behavior (Carnett et al., 2020; Carnett & Ingvarsson, 2016; Howlett et al., 2011; Kahlow et al., 2019; Landa et al., 2017, 2020; Lechago et al., 2010, 2013; Marion et al., 2011, Marion, Martin, Yu, Buhler, & Kerr, 2012; Pyles et al., 2021; Roy‐Wsiaki et al., 2010; Shillingsburg et al., 2018, 2019; Somers et al., 2014; Speckman et al., 2021; Valentino et al., 2019), and the authors of 12 experiments reported those assessment results (all but Howlett et al., 2011; Lechago et al., 2013; Shillingsburg et al., 2018; Somers et al., 2014). The authors of all 35 experiments reported anecdotal information for each participant's existing verbal repertoire (e.g., can tact more than 100 items; can mand for information using wh‐ questions, but does not mand for information using how?…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations